Kepemimpinan Transformasional, Kepuasan Kerja dan Komitmen Organisasi - Susiawan, Susilo; Muhid, Abdul (Persona:Jurnal Psikologi Indonesia, 2015)
This study aims to examine the relationship between transformationalleadership and job satisfaction and organizational commitment. Subjects wereemployees of the production division of PT. Barata Indonesia (Persero) Gresiktotaling 30 people. Data were obtained using a scale of organizational commitment,scale transformational leadership and job satisfaction scale. Based on the analysis ofdata by multiple regression unknown regression F value = 24.063, p = 0.000 (p<0.001), which indicates that there is a very significant positive relationship betweentransformational leadership and job satisfaction and organizational commitment.Thus, the hypothesis "There is a relationship between transformational leadershipand job satisfaction and organizational commitment" is acceptable. The coefficient ofdetermination (R square) amounted to 0,641, which means the effective contributionof the two predictors of transformational leadership and job satisfaction onorganizational commitment criterion amounted to 64.1%. While the remaining 35.9%influenced by other variables not included in this studyKeywords : transformational leadership, job satisfaction, organizational commitment